Engineering of Syndiotactic and Isotactic Polystyrene-Based Copolymers via Stereoselective Catalytic Polymerization - Laur, Eva (Molecules, 2017)
This contribution presents an updated overview of the different copolymers containing stereoregular polystyrene blocks. Special emphasis is placed on syndiospecific and isospecific copolymerization of styrene with co-monomers (ethylene and α-olefins, conjugated and non-conjugated dienes, styrene derivatives, etc.). The catalytic systems involved are described and the polymerization mechanisms are discussed. Alternative approaches (simultaneous, living, chain-transfer and graft copolymerization) and the resulting detailed structures and characteristics of the copolymers are also reported.